PERENCANAAN LAYOUT PARKIR DI RUMAH SAKIT GIGI DAN MULUT (RSGM) UDAYANA - I Made Kariyana; Tri Hayatining Pamungkas; Ni Made Ola Ulandari; Putu Aryastana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
The Dental and Oral Hospital (DOH) of Udayana is the hospital owned by Udayana University which is located at the Udayana Jimbaran Campus. The DOH of Udayana can be categorized as a new hospital because the construction of this hospital is still in the non-finishing structure stage, so it doesn’t have parking facilities. In this study, planning of the parking layout for Udayana DOH was carried out to get an optimal parking design in terms of parking capacity, vehicle type, and parking space needs based on land availability. The number of parking space units was determined based on the number of beds that follow the provisions in the Regulation of the Directorate General of Land Transportation No. 272/HK.105/DRJD/1996, while the percentage of vehicle type composition was analyzed through a survey comparison and interviews at DOH of Saraswati Denpasar. The survey comparison result depicts that the percentage of vehicle types parked for motorcycles and cars is 92.45% and 7.55%, respectively. The number of parking space units required based on the number of beds is 104 units, so the composition of the number of parking spaces for motorcycles and cars is 96 and 8, respectively.